Gradient dopant profiling and spectral utilization of monolithic thin-film silicon photoelectrochemical tandem devices for solar water splitting. Issue 8 (26th November 2014) - Han, Lihao; Digdaya, Ibadillah A.; Buijs, Thom W. F.; Abdi, Fatwa F.; Huang, Zhuangqun; Liu, Rui; Dam, Bernard; Zeman, Miro; Smith, Wilson A.; Smets, Arno H. M.
Abstract : A cost-effective and earth-abundant photocathode based on hydrogenated amorphous silicon carbide (a-SiC:H) is demonstrated to split water into hydrogen and oxygen using solar energy. Abstract : A cost-effective and earth-abundant photocathode based on hydrogenated amorphous silicon carbide (a-SiC:H) is demonstrated to split water into hydrogen and oxygen using solar energy. A monolithic a-SiC:H photoelectrochemical (PEC) cathode integrated with a hydrogenated amorphous silicon (a-SiC:H)/nano-crystalline silicon (nc-Si:H) double photovoltaic (PV) junction achieved a current density of −5.1 mA cm −2 at 0 V versus the reversible hydrogen electrode. The a-SiC:H photocathode used no hydrogen-evolution catalyst and the high current density was obtained using gradient boron doping. The growth of high quality nc-Si:H PV junctions in combination with optimized spectral utilization was achieved using glass substrates with integrated micro-textured photonic structures. The performance of the PEC/PV cathode was analyzed by simulations using Advanced Semiconductor Analysis (ASA) software.